Underutilization of IV Nitrates in the Treatment of Acute Heart Failure. Issue 4 (7th July 2015) - Mohan, Mohapradeep; Hawkey, Sean; Baig, Fatima; Choy, Anna Maria; Lang, Chim C.
Summary Acute heart failure (AHF) is a growing public health concern with high inhospital mortality and costs. Clinical practice guidelines, underpinned by positive randomized controlled trials, recommend the early use of intravenous (IV) nitrates in the treatment of AHF. However, the "real‐world" usage of IV nitrates has not been clearly defined. The objective of this study was to examine the use of IV nitrates in the treatment of AHF as recommended by clinical practice guidelines. A case‐record analysis was conducted of all admissions with AHF at a large teaching hospital. Of the 81 AHF patients (mean age 77 ± 11, mean SBP 130 ± 27 mmHg) enrolled for this analysis, only 5 (6%) received IV nitrates at the time of AHF admission. Forty (49%, mean age 77 ± 11, mean SBP 131 ± 27 mmHg) of these 81 patients met the guideline criteria for suitability for IV nitrates and only 5 (12%) of these received them during this admission. Patients who received IV nitrates were more likely to have higher blood pressure and all had myocardial ischemia as a precipitant. Seventy‐five (93%) of the total population received loop diuretics on admission. Overall, this study shows that loop diuretics remain the first‐line therapy in AHF with little use of IV nitrates, despite recommendations from clinical practice guidelines.